Estudo sobre a burocracia de rua do Programa Estrutural em Área de Riso da Prefeitura Municipal de Belo Horizonte - Josiane Bragato (2012)
This is a study about street-level bureaucracy from the analysis of the daily work performed by technical area of physical and social, bureaucrats implementers, of the Program in Structural Risk Areas, coordinated by Urbanization Company of Belo Horizonte, an agency of the Municipality of Belo Horizonte.The phenomenon of street-level bureaucracy to be analyzed consists of the construction logic of the actions of street-level bureaucrats, within specific working conditions that affect the routine of their services with citizens and / or customers. Act is to explain how the street-level bureaucrats, in the opinion of an actor, to preserve the social order of his agency and its service.We look at this study, for the apprehension of the implementation details, considering that it is a complex process driven by bureaucrats implementers that involves people, rules, relationships, skills, experiences, interactions, conceptions, interests, values, wills , needs, power, resources, conflicts, styles, attitudes, knowledge and unknowns.